Naqd Abī Ḥayyān al-Naḥwī li Ibn Mālik: Dirāsah Muqāranah bayna al-Fikr al-Naḥwī li Abī Ḥayyān wa al-Fikr al-Naḥwī li Ibn Mālik - Nulhakim, Lukman; Ilmi, Vika Wafa (Al-Zahra : Journal for Islamic and Arabic Studies, 2024)
The Alfiyyah by Ibn Malik is highly renowned in the Islamic world, including Indonesia, particularly in traditional pesantren, as a primary reference for Arabic grammar. However, this monumental work is not without criticism. One of its critics is Abu Hayyan al-Nahwi, an Andalusian linguist, who expressed his critique in his book Manhaj al-Salik fi al-Kalam ‘ala Alfiyyah Ibn Malik. Abu Hayyan highlighted various issues in Alfiyyah, particularly regarding anomalous data, which he believed were often based on weak opinions or rarely transmitted sources. In his preface, Abu Hayyan stated that Ibn Malik “chose what is unfamiliar and abandoned the majority of grammarians' views.” This study aims to explore Abu Hayyan's critique of the anomalous data in Alfiyyah through a qualitative descriptive approach based on library research. The findings reveal six main reasons behind Abu Hayyan's critique: Ibn Malik’s interpretations were speculative, his claims of anomaly involved data that were actually eloquent, deviations from the principle of relying on authoritative linguistic sources, analogies drawn from data outside their context, a tendency to favor minority opinions, and inconsistencies in grammatical rules. This critique reflects Abu Hayyan’s effort to establish a more accurate and reliable framework for deriving grammatical rulings.